On the rate of the volume growth for symmetric viscous heat-conducting gas flows with a free boundary (Abstract and Applied Analysis)
The system of quasilinear equations for symmetric flows of a viscous heat-conducting gas with a free external boundary is considered. For global in time weak solutions having nonstrictly positive density, the linear in time two-sided bounds for the gas volume growth are established.